Participation in continuing vocational training in Germany between 1989 and 2008 - Alexander Yendell (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Who participates in continuing vocational training and who does not? This central question in research on continuing vocational training gains in significance the more the importance of lifelong learning is postulated. On the basis of the SOEP data collection periods of 1989, 1993, 2000, 2004 and 2008, I will describe participation in continuing vocational training in Germany between 1989 and 2008, and explain this participation according to two prominent theories derived from the economics of education - the human capital theory and the theory of labour market segmentation.
Keywords: I24; 330